Effect of mobile structured educational applications on self-care management in diabetes mellitus patients - Darma Karingga, Devangga; Efendi, Ferry; Indarwati, Retno; Bushy, Angeline (Gaceta Médica de Caracas, 2023)
Introduction: Self-care management is carried out independently by Diabetes Mellitus (DM) patients to meet their needs and control blood glucose. The inability to manage the disease independently can cause complications in people with DM. This study aims to determine the effect of structured educational applications to improve self-care management in people with DM. Methods: The research design was a quasy experimental. The research sample was Type 2 DM which, according to the inclusion and exclusion criteria, consisted of 134 people divided into the control and intervention groups. Data collection was carried out using a self-care management questionnaire. Data analysis used a statistical test to assess the effect of the intervention on the patient.